The complete chloroplast genome sequence of common Chinese ivy Hedera nepalensis var. sinensis (Araliaceae) - Jun-Jie Wu; Xuan Zhou; Jing Gao; Yong-Qing Peng; Shu-Hang Hu; Ying-Xi Qian; Cong Zhang; Rui-Hong Wang; Zhe-Chen Qi (Mitochondrial DNA. Part B. Resources, 2019)
The complete chloroplast genome of widely cultivated Hedera nepalensis K. Koch var. sinensis (Tobl.) Rehder was sequenced and assembled in this study. The genome is 156,652 bp in length and contained 134 encoded genes in total, including 87 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. Based on available plastomes of 13 species in Araliaceae, we reconstructed their phylogenetic relationships and found that H. nepalensis var. sinensis is closely related to Fatsia japonica.